2018
DOI: 10.1002/chem.201706136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in Iodine Catalysis

Abstract: Molecular iodine has been used for more than 100 years as a remarkable catalyst for many organic transformations such as cycloadditions, Michael and aldol reactions, or esterifications. Different explanations for the origin of its catalytic effect have been proposed in the last decades including a "hidden" Brønsted acid catalysis by HI, a Lewis-acid (or halogen-bond) activation, or catalysis by an iodonium(I) species. Recently, iodine catalysis again gained more interest due to the latest developments in halog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(95 citation statements)
references
References 179 publications
3
87
0
5
Order By: Relevance
“…In order to increase the yield of the reaction, four kinds of transition metal copper and palladium catalysts were evaluated, but no reaction occurred (18)(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the yield of the reaction, four kinds of transition metal copper and palladium catalysts were evaluated, but no reaction occurred (18)(19)(20)(21).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, it was noticed that iodine is an active catalyst and even offers milder reaction conditions . [17] These reactions are explained by hidden bronsted acid catalyst caused by decomposition of HI . We presume that N ‐methylaniline primarily reacts with an aldehyde in the presence of iodine to produce iminium ion.…”
Section: Resultsmentioning
confidence: 99%
“…Intermediates of the s-alkyl-iodine(III) series are formed commonly throughout catalytic reactions, when thesei nclude the application of aryliodine(III) catalysts tates. [47] Such ac oncept envisionsi odine catalysis [48] that departs from an iodine(III) catalyst state at the outseto ft he functionalization of the hydrocarbon substrate (Figure 4, left). Prominent examples to this end are catalytic alkene difunctionalization and oxidation reactions of enolates.…”
Section: Applications In Catalysismentioning
confidence: 99%
“…Although it appears ar easonable general strategy,i ts application remains under-developed.I nfact, although not elucidated in depth, several of the existing catalytic oxidation reactions originating from the combinationo fm olecular iodine or an inorganic iodine salt with at erminal oxidant such as H 2 O 2 , tBuOOH, mCPBA may involvealkyliodine(III) catalyst states. [48] Following the stoichiometrict ransformationsb yA sensio, [38] the use of alkyliodine(I)d erivatives as sources forh omogeneous iodine catalysts was explored by Shafir andP leixats (Scheme 13). [49] They demonstrated that extrusion through 64 of an inorganic iodine(I) or/and iodine(III) from different iodoalkanes 63 such as 2-butyli odide, generates an active iodine speciest hat catalyzes the a-tosyloxylation of ketones 65 to 66 in the presence of mCPBA as terminal oxidanta nd RSO 3 Ha s nucleophile.…”
Section: Applications In Catalysismentioning
confidence: 99%